Durability of sandstones from Sub-Himalaya of central Nepal - Budhathoki, Aadesh; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2022)
The Sub-Himalaya of Nepal experiences sub-tropical climate where geologically young and delicate sedimentary rocks are prone to chemical and physical weathering and consequent erosion. The main aim of this study is to identify and evaluate the durability characteristics of some sandstones against slaking, freezing-thawing and abrasion. Lithosomes were characterized in the field. The following laboratory tests included measurements of dry density, specific gravity, water absorption, Slake Durability Index (SDI), Sulphate Soundness (SS), and Los Angles Abrasion (LAA). Sandstones from the Lower Siwalik Subgroup (LSS) are massive to cross-stratified, very fine- to medium-grained, and occasionally calcareous, whereas the sandstone from the Middle Siwalik Subgroup (MSS) are mostly cross-stratified to few massive, medium- to coarse-grained with salt-and-pepper appearance, and uncommonly calcareous. Sandstones have four different types of deterioration and had high to extremely high SDI. The majority of the sandstones have displayed similar slaking tendencies. Under the five-cycle SS test, the majority of sandstones from LSS and MSS have experienced low final weight loss (below 10%). However, two from LSS and three from MSS have experienced greater final weight loss. The LAA values range from 29.66% to 99.14%, and except two sandstones from LSS, rest of the samples have exceeded 45% abrasion showing they were incompetent in terms of abrasion test, and are highly susceptible to abrasion. The uniformity factor ranges from 0.21 to 0.44 indicating that all the sandstones were of non-uniform hardness. Correlation among physical parameter and durability indices was weak to moderate probably because of varied nature of sandstones.